A Review on Tea Leaves and Tea Fibre as Adsorbents for Heavy Metals Removal - A, Undie David; E, Etim Emmanuel; S, Samuel Humphrey; Yakubu, Shedrach (Science Tech Group, 2024)
Heavy metal pollution is a significant environmental concern due to its detrimental effects on ecosystems and human health. The conventional techniques for the eliminating heavy metals from water-based solutions, like chemical precipitation and ion exchange, have certain drawbacks in terms of effectiveness, expenses, and ecological impact. In recent years, researchers have explored the use of natural materials, including tea leaves and tea fibre, as alternative adsorbents for heavy metal removal. From research, tea leaves and tea fibre, derived from the camellia sinensis plant, have emerged as promising adsorbent due to their abundance, low cost, and potential for heavy metal adsorption from aqueous phase. This comprehensive review aims to summarize and evaluate the current state of knowledge regarding the use of tea leaves and tea fibre in the removal of heavy metals from aqueous solutions. It will discuss the adsorption mechanisms, influencing factors, and potential applications of these natural materials. The research will also covers a comparative analysis of this adsorbent with other adsorbents, isotherms, kinetics and equilibrium studies, as well as regeneration and reusability of tea-based adsorbents.